A randomized controlled trial on the effectiveness of the abridged illness management and recovery program for people with schizophrenia spectrum disorders - Raymond Hung Kei Wong; Raymond Wing Cheong Au; Chan Wai Lan; Chiu Pi Fan; Frank Pi Fan Chiu; Mann Man Keung Chu; Thomas Chung Lung Kong; Ada Wai Yu Lo; Donald Chi Shing Mak; Justina KP Wong; Sharifa YP Yam (SAGE Publishing, 2023)
Objective This study aimed to investigate the effectiveness of an abridged version of the Illness Management and Recovery Programme (AIMR) that was modified and developed in Hong Kong through a mult-centre randomized controlled trial for patients with schizophrenia spectrum disorders. Methods This study was implemented in 10 occupational therapy departments, psychiatric day hospitals of 7 Hospital Authority clusters in Hong Kong. A total of 211 patients with schizophrenia or schizoaffective disorder was recruited and randomized into either the experimental or the control condition. In the control group, the subjects went through conventional occupational therapy programmes. In the experimental group, the subjects went through an additional 10-session programme of AIMR. Participants were measured at baseline, completion of the AIMR, and 3-month after the AIMR programme. Measures include the expanded version of the Brief Psychiatric Rating Scale (BPRS-E), the client version of the Illness Management and Recovery Scale (IMRS), the Snyder Hope Scale, the Social and Occupational and Occupational Functioning Assessment Scale (SOFAS), the WHO Quality of Life Scale (WHOQOL-BREF), and the Chinese Version of the Short Warwick-Edinburgh Mental Well-Being Scale (C-SWEMWBS). Results Both the experimental and control cohorts had comparable clinical and socio-demographic characteristics except years of education and duration of illness. These two variables were entered as covariates in the linear mixed model which showed that the experimental group had significantly higher improvement than the control group in terms of illness management (F = 4.82; p = .03; Cohen's d = .45), functional (F = 10.65; p = .001; Cohen's d = .58), and hope (F = 5.52; p = .02; Cohen's d = .08) measures after the completion of treatment. Conclusion The results supported the effectiveness of the AIMR programm which would be important in the recovery oriented practices in psychiatry.